Synthesis, Characterization, and Antimicrobial Properties of a New Ligand and Its Pd(II), Ru(II), Fe(II), Co(II) Complexes - Kenan Buldurun; Nevin Turan; Yusuf Alan; Naki Çolak (Düzce Üniversitesi Bilim ve Teknoloji Dergisi)
Schiff bases and their complexes are versatile compounds synthesized from the condensation of an amino compound with carbonyl compounds and widely used for industrial purposes and also exhibit a broad range of biological activities including antifungal, antibacterial, antimalarial, antiproliferative, antiviral, and antipyretic properties. In this study, the complexes of (E)-2-(3,5-di-tert-butyl-2-hydroxybenzylideneamino)-6-methyl-4,5,6,7-tetrahydrobenzo[b]thiophene-3-carbonitrile (L) with Co(II), Fe(II), Pd(II) and Ru(II) were successfully prepared. Structures of Schiff base and its metal complexes obtained were confirmed by FT-IR, 1H-NMR, 13C-NMR, UV–vis, magnetic susceptibility, mass spectroscopy and elemental analysis. The synthesized Schiff base and its metal complexes were tested for antimicrobial activity against Enterobacter aerogenes, Bacillus subtilis, Staphylococcus aureus, Bacillus megaterium, Pseudomonas aeroginosa, Klebsiella pneumoniae, Escherichia coli, Candida albicans, Yarrowia lipolytica and Saccharomyces cereviciae. When the antimicrobial activities of the compounds were examined, it was observed that the lowest activity was exhibited by the ligand, and the highest activity was exhibited by the Co(II) and Pd(II) complexes. None of our compounds were been found to exhibit antifungal activity.